THE EXPERIENCES OF TEACHERS AND PARENTS IN USING READING ANTHOLOGIES WITH FOUNDATION PHASE LEARNERS - Martha Khosa (Social Sciences and Education Research Review)
Given the low performance in reading literacy among South African learners, the Department of Basic Education (DBE) created opportunities for the provisioning of isiZulu Home Language (HL) Reading Anthologies (RAS) in the Foundation Phase (FP) (Grades 1-3) classroom. This article aims to examine teachers' and parents' experiences in using these RAs with learners and explores how their sustainable use could be supported. A qualitative case study was used to gather data in six quintile 1 and 2 schools. Grade 1 and 3 teachers were interviewed. Focus group discussions with parents of learners were undertaken in each of the six schools sampled. Interviews revealed the convenience of having one book with multiple selections of stories written in children's HL-making teaching reading in the classroom easier. Group discussions showed that the provision of RAs strengthened parents' involvement in supporting and encouraging their children's reading. In view of these findings, it is recommended that the DBE should continue supporting reading in the FP by sustaining the provisioning of the RAs at home and in the classroom. Hence, effective training and workshops are necessary for teachers and parents to manage and use these resources.